(NgRIM(B:s (NU^EBNOE POSOBIEs - (Ns(B.(Ni(B.(NnEPEJWODAs ((NsANKT(B-(NpETERBURGs (NlAN_s (NpLANETA MUZYKAs, 2019)
(Nu^EBNOE POSOBIEMPREDSIAWLQET SOBOJ IZLOVENIE OSNOWNYH PRINCIPOW PO ISKUSSTWU TEATRAL_NOGO GRIMA(B.s
Keywords: (NISKUSSTWAs